Case report: A novel truncating variant of BCL11B associated with rare feature of craniosynostosis and global developmental delay - Zhao, Xuemei; Wu, Bingbing; Chen, Huiyao; Zhang, Ping; Qian, Yanyan; Peng, Xiaomin; Dong, Xinran; Wang, Yaqiong; Li, Gang; Dong, Chenbin; Wang, Huijun (Frontiers in Pediatrics, 2022)
Craniosynostosis is a premature fusion of cranial sutures, resulting in abnormally shaped skull and brain development disorder. The description of craniosynostosis in patients with BCL11B mutations is rare. Here, we firstly report a 25-month-old Chinese boy with a novel frameshift variant in BCL11B gene. The patient was identified c.2346_2361del by whole-exome sequencing and was confirmed to be de novo by parental Sanger sequencing. This patient presented clinical phenotype of craniosynostosis as well as global developmental delay. He had a small mouth, thin upper lip, arched eyebrows, a long philtrum, midfacial hypoplasia and craniosynostosis. Brain MRI showed brain extracerebral interval and myelination changes, and brain CT with 3D reconstruction showed multi-craniosynostosis. Our study expands the clinical phenotypes of patients with BCL11B gene mutation, and our findings may help guide clinical treatment and family genetic counseling.